SALNAMELERE GÖRE SİVAS VİLAYETİNDE DİNİ VE SOSYAL YAPI - GENÇ, EROL (Fırat Üniveristesi, 2009)
XVI. yüzyılda beylerbeyi merkezi, daha sonra Osmanlı vilayet sistemi içerisinde önemli bir vilayet merkezi olan Sivas, Anadolu medeniyetine ev sahipliği yapmış bünyesinde, İslam, Yahudilik ve Hıristiyan mezheplerine mensup inanlıları barındırmıştır.Salnamelere göre Sivas vilayetinde Müslümanların dini ve sosyal kurumlarının yanında gayri müslimlerin de kendilerine ait dini ve sosyal kurumları bulunmaktadır. Sivas vilayet genelinde gayri müslimlere ait okullar ve ibadethaneler her dönem varlığını sürdürmüştür.Sivas vilayetinde yaşayan toplam nüfusu Müslim, gayri müslim oranlamasıyla merkezden başlamak üzere sancak ve kazalar şeklinde tablolar halinde vererek, bölgede yaşayan dini grupların nüfusları ortaya konmuştur.

It is the centre of beglerbeg (gouernor-general) in XVI. century, which has become an important centre of province in Ottoman province system later, Sivas hosted the Anatolian civilization sheltered members of Islam, Jewish, Christian sects in its free atmosphere respected to religions in itself.In respect of yearbooks, there used to be religious and social institutions of Muslims, besides, there also used to be religious and social institutions belonging to non-muslims in Sivas pravince. In the whole Sivas province, school and places of worships belong to non-muslims carried on their existence all time.The population of religious groups living in the area brought up in tables beginning from the centre then as sanjaks and subdivisions of province with the rate of Muslim, non-muslim total population living in Sivas province.
Religious and social structure in Sivas province in respect of yearbooks
Keywords: Din